2002
DOI: 10.1007/s101620010071
|View full text |Cite
|
Sign up to set email alerts
|

Topological and Developmental Gradients of Calbindin Expression in the Chick's Inner Ear

Abstract: ABSTRACTexpression two days later. Immunoreactivity appeared in abneural supporting cells days later than in hair cells, and not until E20 in neurally located supporting Mobile intracellular calcium buffers play an important cells. These results demonstrate that calbindin mesrole in regulating calcium flux into mechanosensory sage and protein levels are greater in high-frequency hair cells and calbindin D-28k is expressed at high hair cells. This "tonotopic" gradient may result from levels in the chick's basil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 56 publications
5
19
1
Order By: Relevance
“…Actin was detected by our array but found not to be tonotopically expressed (data not shown), a finding that is intuitive given that the total amount of actin per hair cell does not vary tonotopically in chickens (Tilney and Tilney 1988). The calcium binding protein calbindin was previously found to be expressed at higher levels in basal than in apical hair cells (Navaratnam et al 1995;Navaratnam et al 1997;Hiel et al 2002), a finding that was not confirmed by our microarray data. However, this observation is likely the result of the 3′ bias of the Affymetrix chicken array.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Actin was detected by our array but found not to be tonotopically expressed (data not shown), a finding that is intuitive given that the total amount of actin per hair cell does not vary tonotopically in chickens (Tilney and Tilney 1988). The calcium binding protein calbindin was previously found to be expressed at higher levels in basal than in apical hair cells (Navaratnam et al 1995;Navaratnam et al 1997;Hiel et al 2002), a finding that was not confirmed by our microarray data. However, this observation is likely the result of the 3′ bias of the Affymetrix chicken array.…”
Section: Discussioncontrasting
confidence: 92%
“…In contrast, previous work showing tonotopicity of calbindin expression used qPCR primers designed to amplify a portion of the transcript that is present in all 25 variants, and these results are therefore much more reliable (Navaratnam et al 1995(Navaratnam et al , 1997Hiel et al 2002). That calbindin was not found by microarray to be tonotopically expressed therefore likely reflects the spatial distribution of an exceedingly rare splice variant.…”
Section: Tablementioning
confidence: 82%
“…It is not surprising therefore that calmodulin (CaM) has been identified in the cochlea of gerbil (Nakazawa, 2001) and guinea pig (Furness et al 2002), and that calbindin-D28-K (CaB) has been found in the primate (Usami et al 1995) and chick (Hiel et al 2002) inner ear, in the dog cochlea (Coppens et al 2000) and in the otoconia of the musk shrew (Karita et al 1999). In the lizard Podarcis sicula , CaB is present on the outer surface, in the central core (Balsamo et al 2000) and in the organic matrix of otoconia (Piscopo et al 2003(Piscopo et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Calbindin, encoding a calcium binding protein, is expressed strongly in basal hair cells and this expression gradually becomes weaker in hair cells toward the apex of the BP (Fig. 3C) (22). Graded levels of Calbindin expression in hair cells are postulated to be required for calciumdependent, frequency-specific responses along the tonotopic axis of the BP (22).…”
Section: Resultsmentioning
confidence: 99%